Eksistensi Hakim Menurut Al-Qur’an - Anwar Sadat (AL-Fikr, 2011)
This article covers about a judge in the view of Remembrance and its relevance to the existence of judges in the present. The method used is a library research that is by examining a number of literature directly related to the focus problem. The results showed that the profession of judges which also is a matter of proud achievement. In neighboring countries like Malaysia and Singapore, a district judge is said to be more respected and authoritative than a regent, or mayor. Charisma is remarkable, because there the judge regarded as a semigod.